On the φ-index of inclusion: studying the structure generated by a subset of indexes. - Madrid-Labrador, Nicolás Miguel; Ojeda-Aciego, Manuel; Ramírez-Poussa, Eloisa (Wiley, 2025)
The φ-index of inclusion has proven to be a suitable generalization of the inclusion in the fuzzy setting. In this paper, the properties of the φ-index of inclusion, when its definition is restricted to a subset of indexes, are analyzed. The theoretical results obtained in this work are necessary in order to develop fuzzy inference systems based on the φ-index of inclusion.
https://openpolicyfinder.jisc.ac.uk/id/publication/7516
Keywords: Conjuntos difusos; f-inclusion